2019
DOI: 10.1007/s10815-018-1358-3
|View full text |Cite
|
Sign up to set email alerts
|

In assisted reproduction by IVF or ICSI, the rate at which embryos develop to the blastocyst stage is influenced by the fertilization method used: a split IVF/ICSI study

Abstract: Purpose To compare in vitro fertilization (IVF) with intracytoplasmic sperm injection (ICSI) in regard to post-fertilization development and outcome with the purpose of ascertaining the most effective fertilization method for assisted reproduction. Methods A retrospective cohort study of 136 split IVF/ICSI cycles (where sibling oocytes are fertilized by two different methods using the same sperm sample). Results IVF-derived embryos developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…In concordance with our results analyzed in their globality and by sub-groups, previous authors applying split insemination found significant higher fertilization rate in ICSI compared to IVF [11,[15][16][17]28], comparable cleavage rate [10-12, 14, 15, 20], no statistical difference in blastocyst rate [11,13], comparable implantation [10,12] and live birth rates [13,16].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with our results analyzed in their globality and by sub-groups, previous authors applying split insemination found significant higher fertilization rate in ICSI compared to IVF [11,[15][16][17]28], comparable cleavage rate [10-12, 14, 15, 20], no statistical difference in blastocyst rate [11,13], comparable implantation [10,12] and live birth rates [13,16].…”
Section: Discussionsupporting
confidence: 92%
“…Previous authors applying split insemination reported data from embryo development until cleavage stage [ 10 , 12 , 15 , 16 ] or on a minor number of cases [ 11 , 13 , 14 , 18 , 28 ]. The present study is the first one focused mainly on blastocyst stage, and on such a high number of cases that could also be analyzed according to different clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IVF revolutionised infertility treatment, poor semen quality remains associated with poor outcomes in IVF (Stephens et al, 2013). ICSI involves the injection of a single spermatozoon into the oocyte; thus, it represents the gold standard technique in case of cryptozoospermia (Palermo et al, 1992(Palermo et al, , 2017, whereas in IVF, a minimum seminal concentration of 200,000 motile spermatozoa/mL is required for fertilization (Speyer et al, 2019).…”
Section: Despite Its Advantages Macs Is Yet To Be Certified By the Fmentioning
confidence: 99%
“…ICSI has been successfully applied to overcome severe male factor infertility presentations, including oligozoospermia, asthenozoospermia and teratozoospermia, or a combination of these, as well as in case of recurrent IVF failures (Palermo, Neri, Schlegel, & Rosenwaks, 2014;Speyer et al, 2019). Furthermore, ICSI bypasses sperm kinetic defects, the presence of anti-sperm antibodies, acrosome dysfunction and the lack of maturity in gametes collected directly from the epididymis or testicles (Palermo et al, 2014).…”
Section: Despite Its Advantages Macs Is Yet To Be Certified By the Fmentioning
confidence: 99%